Towards an understanding of global brain data governance: ethical positions that underpin global brain data governance discourse - Ochang, Paschal; Eke, Damian; Stahl, Bernd Carsten (Frontiers in Big Data, 2023)
The study of the brain continues to generate substantial volumes of data, commonly referred to as 'big brain data,' which serve various purposes such as the treatment of brain-related diseases, the development of neurotechnological devices, and the training of algorithms. This big brain data, generated in different jurisdictions, is subject to distinct ethical and legal principles, giving rise to various ethical and legal concerns during collaborative efforts. Understanding these ethical and legal principles and concerns is crucial, as it catalyses the development of a global governance framework, currently lacking in this field. While prior research has advocated for a contextual examination of brain data governance, such studies have been limited. Additionally, numerous challenges, issues, and concerns surround the development of a contextually informed brain data governance framework. Therefore, this study aims to bridge these gaps by exploring the ethical foundations that underlie discussions on brain data governance. It does so by conducting a secondary analysis of interviews with neuroscientists representing a global perspective and employing ethical theories. Ethical theories provide the philosophical frameworks and principles that inform the development and implementation of data governance policies and practices. The results of the study reveal various positions that underscore the ethical perspectives of neuroscientists engaged in brain data research. This research highlights the multitude of challenges and deliberations inherent in the pursuit of a globally informed framework for governing brain data. Furthermore, it sheds light on several critical considerations that require thorough examination in advancing global brain data governance.